Neutron Star–White Dwarf Merger as One Possible Optional Source of Kilonova-like Emission: Implications for GRB 211211A - Xiao-Xuan Liu; Hou-Jun Lü; Qiu-Hong Chen; Zhao-Wei Du; En-Wei Liang (The Astrophysical Journal Letters, 2025)
Long-duration GRB 211211A, which lacked an associated supernova at very a low redshift z = 0.076 but was associated with a possible kilonova emission, has attracted great attention. The neutron star–white dwarf (NS–WD) merger is proposed as a possible progenitor of GRB 211211A, and it could naturally explain the long duration of the prompt emission. However, the NS–WD merger is not an ideal site for producing heavy elements via r -process nucleosynthesis. In this Letter, we investigate the heavy elements produced in NS–WD mergers based on numerical simulations of nucleosynthesis via SkyNet and then calculate the resulting kilonova-like emission to compare with the solidly observed case of possible kilonova emission associated with GRB 211211A. By adopting three models (i.e., Model-A, Model-B, and Model-C) from M. A. R. Kaltenborn et al. at different temperatures ( T = 4, 5, and 6 GK), which are treated as free parameters, we find that the mass number of the heaviest element produced in our simulations is less than 90 ( A  < 90). Moreover, by comparing the calculated kilonova-like emission with the afterglow-subtracted observations of the possible kilonova associated with GRB 211211A, it is found that the merger of an NS and WD cannot be ruled out as the origin of GRB 211211A to produce the possible kilonova emission if the remnant of the WD–NS merger is a supramassive or stable magnetar. Otherwise, it is difficult to explain the early possible kilonova emission following GRB 211211A by invoking the merger of a WD and an NS.